An Introduction to Nepalese Economy - Shrestha, B. P. (Himalayan Review, 2011)
Not necessary. Key words: Nepalese economy The Himalayan Review Vol. 15, 1983-18984 Page: 58-61 Uploaded Date: April 13, 2011